Laicità in progress: conclusioni generali (Stato, Chiese e pluralismo confessionale, 2012)
Il contributo, accettato dal Direttore, riproduce l’intervento di chiusura del convegno di studio organizzato dall’ADEC sul tema “Laicità e dimensione pubblica del fattore religioso – Stato attuale e prospettive” (Bari, Aula Magna “Aldo Moro”, 17-18 settembre 2009).SOMMARIO: 1. Le diverse soglie della laicità – 2. Prevalenza della libertà sulla laicità: i presupposti sistematici – 3. I parametri della relatività – 4. Alcune prospettive per lo studio del diritto ecclesiastico:The Principle of Secularism (laicità) “in Progress”.  General ConclusionABSTRACT: Like the previous national meetings, from the sessions of this Conference one may appreciate the worthwhile link between the academic-scientific experience and the juridical-jurisprudential experience. The homogeneity of contents (as revealed by the academic doctrine) together with the relativity of substantial values (strictly related to the conceptions of liberty, secularism and equality) is not necessary due to be translated into different models of State-religions relationship. The concrete use of normative systems is a clear example of that. These are in fact results that emerge from both the public relevance of religious phenomena and the outcomes given by the overview of legislative works; as the main Italian scholars have already underlined at the national and international level, including the European area.